THE EFFECT OF SELF EFFICACY, GOAL ORIENTATION AND OBEDIENCE PRESSURE ON AUDIT JUDGMENT - Novi Darmayanti; Rindang Nur Anggraeni; Martha Suhardiyah; Judi Suharsono (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2022)
This study aims to determine how much influence Self Efficacy, Goal Orientation and Obedience Pressure have on Audit Judgment. The population in this study is the Inspectorate of Lamongan Bojonegoro Regency. The sampling method used in this research is saturated sampling. Data collection techniques in this study by distributing questionnaires to respondents. The questionnaires distributed were 50 questionnaires with a rate of 46 questionnaires or 92% of the total questionnaires sent. The data were analyzed using the multiple linear regression method and processed with the SPSS Version 25 program. Based on the results of the study, it was concluded that Self Efficacy, Goal Orientation partially had a positive and significant effect on auditor quality, but Obedience Pressure variable had no significant effect on auditor quality. Self Efficacy, Goal Orientation and Obedience Pressure simultaneously have a positive influence on Audit Judgment.Keywords : Audit Judgment, Self Efficacy, Goal Orientation and Obedience Pressure.